DESAIN ALAT PENANGKAP GAS METHAN PADA SAMPAH MENJADI BIOGAS - ., Murjito (Jurnal Gamma, 2009)
Methane capture is very helpful in the development of garbage recycling system to be producedinto bio gas as a substitute for gasoline (petrol), which lately has been difficult to find.This study aimed to design a methane capture waste, low cost and good performance made ofplastic polyethilene for a small scale. This research design produces methane capture-based plasticspolyethilene with the following specifications: biodigester with a total volume of 11 m3, 8.8 m3 ofwet volume, processing time 40 days, fulling material 220 kg / day, total area 18 m2, and has a gasreservoir with dimensions of 4.6 m height, diameter of 0.954 m, the effective volume of 2.5 m3.